2015
DOI: 10.1016/j.anifeedsci.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Glycerin and lecithin inclusion in diets for brown egg-laying hens: Effects on egg production and nutrient digestibility

Abstract: a b s t r a c tThe effects of the inclusion of raw glycerin (GLYC) and lecithin in the diet on egg production, egg quality and total tract apparent retention (TTAR) of dietary components was studied in brown egg-laying hens from 23 to 51 wk of age. The experimental design was completely randomized with six diets combined as a 2 × 3 factorial with two levels of GLYC (0 vs. 70 g/kg) and three animal fat to lecithin ratios (40:0, 20:20 and 0:40 g/kg). Each treatment was replicated eight times and the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…This means that LPC may improve energy utilization in an animal fed a low-energy diet by increasing the fat digestibility or absorption, or other nutrients uptake, as LPC supplementation increases the emulsification of fat or changes the structure of the lipid bilayer of the cell membrane. This is agreement with the results of Beemster et al (2002), Attia et al (2009), Han et al (2010b), Boontiam et al (2017) and Mandalawi et al (2015) who observed improved productive performance and feed efficiency contributed to various phospholipid functions (physiological processes of the reproductive system) by supplementing LPC.…”
Section: Resultssupporting
confidence: 93%
“…This means that LPC may improve energy utilization in an animal fed a low-energy diet by increasing the fat digestibility or absorption, or other nutrients uptake, as LPC supplementation increases the emulsification of fat or changes the structure of the lipid bilayer of the cell membrane. This is agreement with the results of Beemster et al (2002), Attia et al (2009), Han et al (2010b), Boontiam et al (2017) and Mandalawi et al (2015) who observed improved productive performance and feed efficiency contributed to various phospholipid functions (physiological processes of the reproductive system) by supplementing LPC.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, the physical characteristics of the eggs were not affected by the experimental treatments (results not presented), which on average, recorded the following values: 0.41 mm in shell thickness, 11.9 in color score, 5.95 mm in albumin height and 89.3 Haugh units. Similar to what was found in this study, the literature concludes that shell thickness, yolk color or the height of the albumin of the eggs are not affected by the levels of glycerin inclusion in the diets (Swiatkiewicz & Koreleski, 2009Boso et al, 2013Duarte et al, 2014;Mandalawi et al, 2015;Cufadar et al, 2016;Fontinele et al, 2017).…”
Section: Treatmentsupporting
confidence: 86%
“…There are no reports in the literature of the dragging effect of glycerin consumption during the transition period on the subsequent performance of egglaying hens. However, research evaluating glycerin consumption on the productive response of egg-laying hens concludes, in accordance with what was found after the egg-laying peak, that the use of this co-product in diets does not affect feed consumption, not even when it is included in the formulation of diets (Swiatkiewicz & Koreleski, 2009;Boso et al, 2013;Mandalawi et al, 2015) or when it is used to replace oil in the formulation (Cufadar et al, 2016;Kanbur et al, 2017). The previous result has also been found in egglaying quails (Erol et al, 2009;Ghayas et al, 2017).…”
Section: Treatmentmentioning
confidence: 58%
See 1 more Smart Citation
“…So, levels of 70 g · kg −1 of pure glycerine and 35.5 g · kg −1 of semi-pure glycerine were the best for broiler performance. Feed conversion ratio was worse after the addition of 70 g · kg −1 glycerine to the diet, but other production parameters and egg quality were not affected (Mandalawi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%